Identify the Nature of Personal Data and Search for a Suitable Legal Framework to Support it in the Iranian Legal System - mahdieh latifzadeh; Sayyed Mohammad Mahdi Qabuli Dorafshan; Saeed Mohseni; Mohammad Abedi (مطالعات فقه و حقوق اسلامی, 2022)
People use their personal data in different contexts, the use of personal data is inevitable. On the other hand, the protection of personal data is a citizenship right and personal data must be legally protected. Such legal protection is fully achieved by the General Data Protection Regulation (GDPR). This European regulation is the most comprehensive legal framework for the protection of personal data. Despite the importance of personal data protection, many countries do not yet have an independent legal document in this regard or have not yet finalized their draft documents, Iran is also one of these countries that does not have an approved legal document in this regard. Therefore, the present article seeks to introduce a suitable legal framework for the protection of personal data in the Iranian legal system and identify the nature of personal data. The nature of personal data and the right to personal data is special.